Necropolitics and Logics of Power in Forced Sterilizations during the Government of Alberto Fujimori in Peru - Garate Flores, Jhon M. (2024)
This article examines the forced sterilization policy implemented during Alberto Fujimori's government in Peru in the 1990s, analyzing the philosophical implications through the frameworks of necropolitics and biopolitics. It explores how these coercive practices primarily affected rural and economically disadvantaged women, situating this state policy within a logic of control over life and death. The structural violence and systematic discrimination reveal a strategy of state domination and fundamental human rights violations.